Colour polymorphism of cotton bollworm larvae as a function of the type of host plant providing its development - Keszthelyi, Sándor; Orsi-Gibicsár, Szilvia; Pál-Fám, Ferenc; Somfalvi-Tóth, Katalin; Balog, Adalbert (Frontiers in Ecology and Evolution, 2024)
A well-known insect phenomenon is colour polymorphism, from which the species hopes to gain some ecological advantage. Herbivores adapt to the colours of their environment to reduce their chances of becoming prey, while predators use camouflage colours to succeed in hiding from prey. The larvae of the cosmopolitan, highly invasive cotton bollworm (Helicoverpa armigera Hbn., Lep.: Noctuidae) also benefit from this morphological polymorphism. Their fully-develop larvae can take on various colours when feeding on foliage. Our study aimed to determine the host plant-related colour adaptation of H. armigera larvae collected from different plant organs using different spectral analysis methods. Our studies, based on colour analysis of photographic images, showed that the colour of fully-developed larvae of the species is highly correlated with the colour of the damaged nutrient plant. The dominant colours of the larvae show a high similarity with the colours of the consumed host plant parts. The RGB-based analysis confirmed that larval colours are clustered according to the host plant's organs and are mainly located in the yellow and green regions of the visible light spectrum. All these results confirm the extraordinary adaptive capabilities of this invasive species, which, among other things, verify its worldwide distribution.